Analisis Pembelajaran Online terhadap Pencapaian Target Hafalan Al-Qur’an Siswa-Siswi Kelas II SDIT Cordova 3 Kabupaten Tangerang - Tsamrotul Imanah; Rizki Zuliani; Mawardi Mawardi; Nurul Muttaqien; Najib Hasan (Jurnal Halaqah, 2021)
This study aims to identify and analyze the target of memorizing the Qur'an for second grade students in online learning. The method used in this study is a qualitative method, which is to examine and analyze the data objectively according to the data collected in the field. Then the data collected from the research results are described in the form of words. The data analysis was done through observation and interviews. In this study, 1 teacher of tahfidz Qur'an and 20 grade II students became the objects. The results of this study indicate that in online learning there are many factors that affect students not achieving the memorization targets that have been determined by the school, including the media factors used during the online learning process. Many students do not participate in online learning because there is no cellphone that can be used, besides that there is often a loss of signal or data packets that run out quickly. Then the other factor is the lack of guidance from parents from home also affects the achievement of memorization targets. Many students whose parents are busy working so they do not accompany these students when doing online learning. The internal factors of these students also have an effect, such as not focusing on listening to recordings, being lazy to memorize, lazy to repeat what has been memorized, and not submitting it to the tahfidz teacher.